Air yang Kultural dan Ideologis: Konstruksi Naratologis Kuala dalam Hikayat Parang Puting - Riqko Nur Ardi Windayanto (Badan Pengembangan dan Pembinaan Bahasa, 2024)
This research aims to reveal the narratological construction of kuala in the Hikayat Parang Puting so that its cultural and ideological values can be identified. By amalgamating the narratological theory of Mieke Bal and Ansgar Nünning, this research moves dialectically between literary works and Malay culture to reveal this construction. The Hikayat Parang Puting MSS Malay D 3 as the British Library collection that has been transliterated is the data source for gathering linguistic units representing kuala constructions. Methodologically, this data is textually analyzed with attention to its context in literary works and the narratology theories employed. The analysis is further reinforced with literature reviews to correlate the literary data with cultural data beyond the text. This research found that kuala is a geographical element that is spread out, one of which is in Penang. In Penang, Hikayat Parang Puting was produced by Ibrahim. The presence of kuala in the text, thus, cannot be separated from that fact. Similar to the cultural idea of kuala, kuala in the text is perceived by the characters and narrator as a space of power (Hall-Airriess) and a liminal space (Andaya). However, this power does not mean a force; liminal space does not contain spiritual potential, but rather myth. Kuala tends to be constructed as an intermediate location that is connected to a dangerous world as well as a space that is safe from these dangers. Narratively, kuala is also a location that conveys land and sea as two opposing locations in the story. This research ultimately concludes that the cultural and ideological kuala is a geographical object that articulates animistic energies, which can bring both security and danger as well as disasters and safety. This becomes the reality of the meaning and culture offered by the tale. AbstrakPenelitian ini bertujuan untuk menguraikan konstruksi naratologis kuala dalam Hikayat Parang Puting sehingga dapat diketahui nilai kultural dan ideologisnya. Penggunaan teori naratologi dari Mieke Bal dan Ansgar Nünning menjadikan penelitian ini bergerak secara dialektal antara karya sastra dan budaya Melayu untuk mengungkapkan konstruksi itu. Hikayat Parang Puting MSS Malay D 3 koleksi British Library yang telah dialihaksarakan menjadi sumber data untuk menghimpun data satuan-satuan lingual yang merepresentasikan konstruksi kuala. Secara metodologis, data ini dianalisis secara tekstual dengan memperhatikan konteksnya dalam karya sastra dan teori naratologi yang digunakan. Analisis diperkuat pula dengan studi pustaka sehingga data karya sastra dikorelasikan dengan data budaya di luar teks. Penelitian ini menemukan bahwa kuala merupakan elemen geografis yang tersebar, salah satunya, di Penang. Di Penang inilah Hikayat Parang Puting diproduksi oleh Ibrahim. Kehadiran kuala dalam teks, dengan demikian, tidak terlepas dari kenyataan itu. Mirip dengan gagasan budaya tentang kuala, kuala dalam teks dipersepsikan oleh karakter dan narator sebagai ruang kekuasaan (Hall-Airriess) dan ruang liminal (Andaya). Namun, kekuasaan ini tidak berarti kekuatan; ruang antara tidak mengandung potensi spiritual, tetapi mitologis. Kuala cenderung dikonstruksi sebagai ruang antara yang terhubung dengan dunia yang berbahaya sekaligus ruang aman dari bahaya tersebut. Secara naratif, kuala juga menjadi lokasi yang mengantarai daratan dan lautan sebagai dua lokasi yang beroposisi dalam cerita. Penelitian ini pada akhirnya menyimpulkan bahwa kuala yang kultural dan ideologis adalah objek geografis yang mengartikulasikan energi animisme, yang bisa mendatangkan rasa aman dan bahaya juga bencana dan keselamatan. Hal itu menjadi kenyataan makna dan budaya yang ditawarkan oleh hikayat.